Mode of action of poloxamer‐based surfactants in wound care and efficacy on biofilms. Issue 5 (5th June 2018) - Percival, Steven L; Chen, Rui; Mayer, Dieter; Salisbury, Anne‐Marie
Abstract : Surfactants are widely used as detergents, emulsifiers, wetting agents, foaming agents, and dispersants in both the food and oil industry. Their use in a clinical setting is also common, particularly in wound care. Complicated or chronic wounds show clinical signs of delayed healing, persistent inflammation, and the production of non‐viable tissue. These types of wounds also present challenges such as infection and potentially house antimicrobial‐tolerant biofilms. The use of wound cleansers to aid cleaning and debridement of the wound is essential. A large proportion of skin and wound cleansers contain surfactants but there is only a small amount of data that shows the effectiveness of them in the enhancement of wound closure. This review paper aims to explore the available literature surrounding the use and mode of action of surfactants in wound healing, in particular Poloxamer 188 (Pluronic F‐68) and Poloxamer 407 (Pluronic F‐127), and also uncover the potential mechanisms behind the enhancement of wound healing and comparison to other surfactants used in wound care. Furthermore, the presence of a microbial biofilm in the wound is a significant factor in delayed wound healing. Therefore, the effect of clinically used surfactants on biofilms will be discussed, with emphasis on poloxamer‐based surfactants.